Preventing Dental Caries in Children : Indian Scenario - Gupta, A; Marya, CM; Dahiya, V; Bhatia, HP; Dhingra, S (Kathmandu University Medical Journal, 2012)
The prevalence of dental caries in developing countries like India is increasing to an alarming level in contrast to developed countries where it has decreased because of variety of preventive measures at the community and individual level. There is no State or Centre funded programs for prevention of dental diseases in India. The present review enlists the targeted prevention of dental caries in permanent teeth of 6 to 16 years old children presenting for dental care. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 77-82 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6920